2012
DOI: 10.1007/s11356-011-0698-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of isoproturon to the food crop wheat as affected by salicylic acid

Abstract: The present results indicate that exogenous SA is able to improve the wheat tolerance to isoproturon toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…Early studies indicated that isoproturon was designed to block the photosystem electron transport in thylakoids at the photosystem II by binding specifically to the quinone site on the D1 protein (dopamine receptor) of the membrane [14,15]. Recent studies have shown that IPU could also be accumulated by other non-target plants and exert detrimental effects on these plants [9,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies indicated that isoproturon was designed to block the photosystem electron transport in thylakoids at the photosystem II by binding specifically to the quinone site on the D1 protein (dopamine receptor) of the membrane [14,15]. Recent studies have shown that IPU could also be accumulated by other non-target plants and exert detrimental effects on these plants [9,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The PCR products were applied to 1% (w/v) agarose gel electrophoresis and stained with ethidium bromide[18].…”
mentioning
confidence: 99%
“…In addition, the growth rates of the ciliate (Tetrahymena pyriformis) and common earthworm (Lumbricus terrestris) were inhibited at 700 g/L or 1.4 g IPU/kg soil, respectively, whereas other Brought to you by | Kungliga Tekniska Högskolan Authenticated Download Date | 7/1/15 10:49 PM of 5 or 50 μm IPU (p < 0.01) ( Figure 5). The GR activity of S. cerevisiae is probably involved in the detoxification of IPU, ensuring the efficient recycling of glutathione to protect cells against phenylurea herbicide, as described in wheat leaves (Triticum aestivum) [28].…”
Section: Resultsmentioning
confidence: 99%
“…salicylic acid, abscisic acid, gibberellins, jasmonic acid, and brassinosteroids) and resistance to toxic compounds (Jensen and Møller, 2010;Mizutani and Ohta, 2010;Cui et al, 2010),. For example, salicylic acid (SA), a regulator of plant response to various environmental stresses (Yang et al, 2003;Liang et al, 2012), has been reported to improve plant resistance to herbicide napropamide toxicity in rapeseed (Brassica napus) (Cui et al, 2010). Cytochrome P450s are known to be involved in detoxification of xenobiotics in the phase I metabolism in plants (Siminszky, 2006;Zhang et al, 2014;Kebeish et al, 2014).…”
Section: Discussionmentioning
confidence: 99%